A Cognitive Perspective on the Luonto Raising Rite of the Karelian and Finnish Ritual Specialists - Kohonen, Siria (Elore, 2024)
Raising one’s luonto has been an essential part of the Karelian and Finnish incantation tradition and is performed by traditional ritual specialists the tietäjät (‘the ones who know’). In this context, luonto (literally ‘nature’) usually means a human’s profound essence, and raising it means activating it somehow. It was considered essential for the success of the incantation rite to performing it with an activated luonto, i.e. behaving in a furious and ecstatic state. Folklorist Anna-Leena Siikala has described this state as a motoric trance that resembles the spirit possession rituals of the Eastern and Central Siberian peoples (Siikala 1992, 208–209). During spirit possession an external spirit is considered to be taking control of a person’s body. Inspired by the Siikala’s description, I examine in this article ways in which raising one’s luonto resembles cross-cultural ways of interpreting certain kinds of behaviour as spirit possession. I concentrate on the ways in which the cognitive processes connected with interpreting spirit possessions can appear in research material. As a theoretical framework, I use anthropologist Emma Cohen’s theory of interpreting spirit possession from the perspective of human cognition (Cohen 2008). The research material comprises narrated folk beliefs, belief narratives and incantations from the 19th and early 20th centuries that are deposited in the Folklore Archive of the Finnish Literature Society. The main research methods used are material-based and theory-based content analysis. This analysis suggests that raising one’s luonto was not usually considered a spirit possession in which an external spirit took control of a person’s body. Rather, this state could sometimes be interpreted as the kind of possession in which an external essence enters the body, although the research material contains some variation on the subject. Karjalais-suomalaisten perinteisten rituaaliasiantuntijoiden eli tietäjien toiminnassa yksi tyypillinen osa loitsurituaalia on ollut tietäjän luonnon ...